Break down the barriers of auto‐inflammation: How to deal with a monogenic auto‐inflammatory disease and immuno‐haematological features in 2022?. Issue 1 (3rd October 2022) - Vergneault, Hélène; Picard, Capucine; Georgin‐Lavialle, Sophie
Abstract: In the past few years, the spectrum of monogenic systemic auto‐inflammatory diseases (MSAID) has widely expanded beyond the typical recurrent fever. Immuno‐haematological features, as cytopenias, hypogammaglobulinemia, hypereosinophilia, lymphoproliferation and immunodeficiency, have been described in association of several MSAID. The objective of this review was to describe these particular MSAID. MSAID must be suspected in front of immuno‐haematological features associated with non‐infectious recurrent fever, chronic systemic inflammation, inflammatory cutaneous manifestations, arthritis or inflammatory bowel disease. Genes and cellular mechanisms involved are various but some of them are of special interest. Defects in actine regulation pathway are notably associated with cytopenia and immune deficiency. Because of their frequency, ADA2 deficiency and Vacuoles, E1‐Enzyme, X‐linked, auto‐inflammatory, Somatic (VEXAS) syndrome deserve to be noticed. ADA2 deficiency results in polyarteritis nodosa‐like presentation with a wide panel of manifestations including cytopenia(s), lymphoproliferation and immune deficiency. Neutrophilic dermatosis or chondritis associated with macrocytic anaemia or myelodysplasia should lead to screen for VEXAS. Of note, most of MSAID are associated with inflammatory anaemia. We proposed here a clinical and pragmatic approach of MSAID associated with immuno‐haematological features. Abstract : In the past few years, the spectrum of monogenic systemic auto‐inflammatory diseases has widely expanded beyond the typical recurrent fever. Immuno‐haematological features, as cytopenias, hypogammaglobulinemia, hypereosinophilia, lymphoproliferation and immunodeficiency, have been described in association of several MSAID. We proposed here a clinical and pragmatic approach of MSAID associated with immuno‐haematological features.